2009
DOI: 10.1111/j.1365-2222.2009.03286.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective Italian survey on the safety of subcutaneous immunotherapy for respiratory allergy

Abstract: In this large prospective study, the rate of SRs was low, thus confirming that injection immunotherapy has an acceptable risk/benefit ratio when prescribed and carried out according to recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 21 publications
1
47
0
2
Order By: Relevance
“…Un estudio reciente describe que el riesgo es mayor en pacientes asmáticos que en los que solo tienen RCA 10 . En cuanto a que la IT produzca una disminución de las enfermedades alérgi-cas a largo plazo, los estudios publicados que describen estos resultados proceden del proyecto Preventive Allergy Treatment Study (PAT) 11 .…”
Section: Comentario Críticounclassified
“…Un estudio reciente describe que el riesgo es mayor en pacientes asmáticos que en los que solo tienen RCA 10 . En cuanto a que la IT produzca una disminución de las enfermedades alérgi-cas a largo plazo, los estudios publicados que describen estos resultados proceden del proyecto Preventive Allergy Treatment Study (PAT) 11 .…”
Section: Comentario Críticounclassified
“…An Italian survey [52], stated an overall rate of systemic reactions in about 5% of patients, and a Spanish survey, which included 423 patients [53] showed a prevalence of 3.7% reactions per patient. A recent multi-centre observational study [54] suggested that systemic reactions are slightly more frequent in rhinitis with asthma than in patients with rhinitis alone, although another retrospective study [55] found no significant association between SRs and asthma. According to the more recent meta-analysis of clinical trials [12], the occurrence of systemic reactions with SCIT (of any type and severity) is about 1 per 9 patients.…”
Section: The Safety Of Slit and Scit In Asthmamentioning
confidence: 99%
“…A systemic reaction was defined as the occurrence of urticaria with or without angioedema, asthma, gastrointestinal symptoms and/or hypotension after the subcutaneous administration of a depot aluminium hydroxide- or calcium phosphate-absorbed airborne allergen extract in subjects who were well and showed a normal clinical examination before the injection. Most systemic reactions were immediate (within 30 min); however, in view of a recent study showing a high prevalence of delayed systemic reactions following injection SIT, reactions occurring within 6 h after the shot were also considered [8]. The severity of adverse reactions was graded based on the symptoms and response to rescue medication, according to the European Academy of Allergy and Clinical Immunology classification [9] revised by the World Health Organization [10] with some modifications, as follows: grade 0 = no symptoms; grade 1 = nonspecific symptoms, probably non-IgE-mediated; grade 2 (mild) = mild rhinitis or asthma, or mild urticaria responding to antihistamines or β 2 bronchodilators; grade 3 (non-life-threatening) = severe urticaria, angioedema and/or severe asthma that responds to treatment; grade 4 (anaphylactic shock) = rapidly evoked reaction including at least 2 out of skin (itching, flushing, erythema, urticaria, angioedema), respiratory (bronchial obstruction, rhinoconjunctivitis), cardiovascular (hypotension or collapse) and/or gastrointestinal symptoms requiring intensive treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Its effectiveness has been demonstrated by a number of properly performed studies and is now generally accepted. Injection SIT is generally considered a fairly safe procedure although systemic adverse reactions may occasionally occur [8]. In clinical practice, most patients undergoing injection SIT show excellent tolerance of the treatment and reach the scheduled high maintenance dose within a relatively short time and limited number of shots.…”
Section: Introductionmentioning
confidence: 99%